Rereading Heterosexuality Feminism, Queer Theory and Contemporary Fiction - Carroll, Rachel (Edinburgh University Press, 2012)
Heterosexuality in contemporary novels, re-examined using the frameworks of feminism and queer theory Drawing on feminist and queer theories of sex, gender and sexuality, this study focuses on female identities at odds with heterosexual norms. In particular, it explores narratives in which the conventional equation between heterosexuality, reproductive sexuality and female identity is questioned. - A timely exploration of the dynamic relationship between feminist and queer theory - Insightful close readings of acclaimed novels, including Jeffrey Eugenides' Middlesex, Zoë Heller's Notes on a Scandal, A. M. Homes' The End of Alice, Kazuo Ishiguro's Never Let Me Go, Alan Warner's Morvern Callar and Sarah Waters' Affinity - Topics range from spinsterhood and intergenerational sexuality to transgender and human cloning